PENGARUH MANAJEMEN PENGETAHUAN TERHADAP KEPEMIMPINAN SERTA IMPLIKASINYA PADA KINERJA PPPK KOTA BEKASI - Fajar Cahyo Utomo (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
This study is conducted to meet the public demand for good public services and the equal to the developed countries, for it is strongly necessary to have professional state apparatus. The variables studied in this research are knowledge and leadership management which associated with PPPK performance in City Government of Bekasi. This research was designed to examine the possibility of causal relationship between variables . The analysis method in this study is using path analysis. The process of collecting data using survey techniques, conducted by submitting statements to respondents in written form or closed questionnaire. Population in this research are PPPK employees in city Government of Bekasi which consists of 98 officer of PPPK that using simple random sampling. The results showed that knowledge management have an indirect effect on PPPK performance, while the leadership is significantly have a direct effect on it. Simultaneously, both variables have a significant effect on PPPK performance. Leadership can not be an intervening variable between knowledge management and PPPK performance, because the value of the total knowledge management influence through leadership is smaller than the value of direct influence on the performance of PPPK.